Long-term successive poultry litter application improves Oxisol fertility in the Brazilian Cerrado (Acta Scientiarum. Agronomy, 2025)
Brazilian Savannah (Cerrado) soils have insufficient nutrient concentrations for attaining high crop yields. Properly applied poultry litter (PL) may improve soil fertility and forage productivity. Herein, we aimed to evaluate the vertical distribution of acidity and nutrient availability in an Oxisol (Latossolo Vermelho distroférrico) subjected to increasing PL doses over 7 years. We determined the vertical distribution and levels of total organic C, total N, Ca, Mg, K, P, and pH in seven soil layers (0–0.05, 0.05–0.10, 0.10–0.20, 0.20–0.30, 0.30–0.50, 0.50–0.75, and 0.75–1.00 m) where four different PL treatments were applied (cumulative levels: 0, 26.32, 43.15, and 57.6 Mg haâˆ’1) over seven years. Potential acidity and low total organic C content indicated the chemical limitations of natural soil. The application of PL reduced soil acidity and increased K, Ca, and Mg levels and base saturation to 1.00-m depth. The highest PL dose (57.6 Mg haâˆ’1) increased the vertical mobility of Ca, K, and Mg while increasing their stocks by 157, 140, and 135%, respectively, in the deeper soil layers. However, even in the long term, the tested PL doses did not increase total organic C, total N, or P levels in the subsurface soil layers. The dual effects of soil acidity correction and improved nutrient content attest to PL application as an effective strategy for improving soil fertility and ensuring sustainable agricultural development in the Brazilian Cerrado.